PEMBUATAN SABUN MANDI PADAT DENGAN PENAMBAHAN EKSTRAK DAUN AVICENNIA MARINA - Widya Pangestika; Satriya Abrian; Rabiatul Adauwiyah (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Negeri Tanah Laut, 2021)
Avicennia marina is a type of mangrove that is widely found in the coastal areas of Pangandaran Beach. In the leaves, there are alkaloid compounds, steroids and tritepenoid which are effective as antibacterial agents, besides that there are also flavonoid compounds that are effective as antioxidants. The antioxidant content in A. marina leaves can be used as a substitute for synthetic antioxidants BHT (butylated hydroxytoluene). Making soap by utilizing the antioxidant content in A. marina leaves was needed to replace synthetic antioxidants replace synthetic antioxidants that could cause allergies to the skin and carcinogenic. In this study, solid bath soap making with the addition of A. marina leaf extract used 4 treatments, namely P1 (0% leaf extract), P2 (2,07% leaf extract), P3 (4,14% leaf extract), P4 (6,21% leaf extract). The tests carried out were physical observation, pH, hedonic, foam height and foam stability, and cleanability test. It was known that the pH of all soap treatments met the standard. The hedonic test gave the result that P2 soap was the most preferred soap, with a score of 6,85. P4 provided the lowest level of foam stability and rigidity. From the overall observation, P2 was the best formulated solid bath soap.